INTRODUCTION OF ROAD CHARGING IN THE CITY OF ZILINA - Pekarova, Jana; Ondrus, Jan (Doprava a spoje, 2008)
Modern transport must ensure the quality of the services and the protection of the environment. With transport problems such as congested streets we can meet today nearly in every bigger city. It arises from the main issue - an increase of individual car traffic in the city centre. One possible solution is the city toll. In recent years, in developed countries city toll is playing more important role when solving traffic problems in cities.